Integrating Network Pharmacology and Experimental Validation to Reveal the Mechanism of Vine Grape Tea Polyphenols on Hyperuricemia-Induced Renal Injury in Mice - Li, Xiaoli; Li, Baoying; Meng, Xinyue; Yu, Fei; Yu, Xin; Zhao, Wenqian; Wang, Yajuan; Gao, Haiqing; Cheng, Mei; Zhong, Lihong (Journal of medicinal food, 2024)
Hyperuricemia (HUA) is a metabolic disease and contributes to renal injury (RI). Vine grape tea polyphenols (VGTP) have been widely used to treat HUA and RI. However, the potential mechanism of VGTP activity remains unclear. To explore the underlying mechanism of VGTP treatment for HUA-induced RI based on network pharmacology that is confirmed by an study. All ingredients of VGTP were retrieved using a Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform and Comparative Toxicogenomics Database systems. The related targets of HUA and RI were obtained from GeneCards and National Center for Biotechnology Information (NCBI) databases. Some ingredients and targets were selected for molecular docking verification. One hour after administering potassium oxonate (300 mg/kg), VGTP (50, 100, and 200 mg/kg/d) was orally administered to HUA mice for 4 weeks. Histopathology and western blotting were performed in renal tissue. Our results showed that VGTP significantly reduced blood urea nitrogen, creatinine, uric acid, and significantly improved the RI and fibrosis of HUA mice. There were 54 active ingredients and 62 targets of HUA-induced RI. Further studies showed that VGTP decreased the expression of Bax, cleaved caspase 3, transforming growth factor- (TGF- 1), CHOP, p-STAT3, and P53, and increased Bcl-2 expression in renal tissue. The related signaling pathways have apoptosis, TGF- 1, P53 and STAT, and endoplasmic reticulum stress (ERS). In this study, VGTP exerted antihyperuricemic and anti fibrosis effects by regulating the apoptosis and ERS signaling pathways. VGTP is expected to become a drug for combating HUA and RI.